The story of Qiu Ju a film by Zhang Yimou - Chen, Yuan Bin (Sony Pictures Home Entertainment, 2006)
In a small Chinese village a farmer (Qing Lai) and his chief quarrel over land. When Qing Lai is injured by the chief, who kicks him in the groin, Qing's wife Qiu Ju begins a quixotic odyssey that takes her from her small village to the provincial capital. She is relentless in her one-woman crusade to wreak a simple justice from the proud Chief ... she wants him to apologize.
Orig.: CHN, HK 1992
Keywords: Civil procedure -- China -- Drama; Humiliation -- China -- Drama; Feature films; Foreign films